Union membership effect on wage premiums: evidence from organized manufacturing industries in India - Amit K. Bhandari (Institute for the Study of Labor (IZA), 2008)
Trade unionism is a legislative system of organizing workers and raising voices for economic and social goods. As the process of global integration deepens the labour market become more flexible and fragmented, rendering collective organization more and more difficult. In this backdrop, the paper attempted to analyse the impact of union membership on wages in the organised manufacturing industries in India. The study uses a recent survey data on labour market in the organised manufacturing industries. The estimated wage premiums for union membership for permanent and contract workers are 56.7 per cent and 10.3 per cent respectively. Decomposing this wage gap indicates that union membership contributes majority of the wage differentials, indicating that unions able to reserve higher premium for their members. In general, it refutes the problem of free riding the benefits in the organized manufacturing industries in India.
urn:nbn:de:101:1-20081114107
Keywords: J51; 330; Trade unions; wage differentials; manufacturing; Lohndifferenzierung; Lohnstruktur; Gewerkschaftlicher Organisationsgrad; Mitgliedschaft; Verarbeitendes Gewerbe; Indien